2008
DOI: 10.4238/vol7-1gmr388
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms involved in folate metabolism and elevated plasma concentrations of homocysteine: maternal risk factors for Down syndrome in Brazil

Abstract: ABstRACt. The aim of the present study was to investigate the effect of polymorphisms C677T and A1298C in the methylenetetrahydrofolate reductase (MTHFR) gene, A2756G in methionine synthase reductase (MTR) gene and A80G in reduced folate carrier 1 (RFC1) gene, and plasma homocysteine (Hcy), on the maternal risk for Down syndrome (DS). Seventy-two DS mothers and 194 mothers who had no children with DS were evaluated. The investigation of the MTHFR C677T, MTR A2756G and RFC1 A80G polymorphisms was performed by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
57
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 43 publications
10
57
1
1
Order By: Relevance
“…Several studies have been conducted on the role of folate gene polymorphisms and metabolism in the pathogenesis of DS to provide evidence and new clues (da Silva et al, 2005;Scala et al, 2006;Wang et al, 2008;Biselli et al, 2008b;Coppedè et al, 2006Coppedè et al, , 2009Neagos et al, 2010;Brandalize et al, 2010). The genes investigated as maternal risk factors for DS include methionine synthase, reduced folate carrier 1 and cystathionine-beta-synthase besides MTHFR and MTRR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been conducted on the role of folate gene polymorphisms and metabolism in the pathogenesis of DS to provide evidence and new clues (da Silva et al, 2005;Scala et al, 2006;Wang et al, 2008;Biselli et al, 2008b;Coppedè et al, 2006Coppedè et al, , 2009Neagos et al, 2010;Brandalize et al, 2010). The genes investigated as maternal risk factors for DS include methionine synthase, reduced folate carrier 1 and cystathionine-beta-synthase besides MTHFR and MTRR.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported that individual polymorphism may be insufficient to cause an increased incidence of birth of children with DS, but that a genotype in which two or more polymorphisms in distinct enzymes of the pathways may lead to increased incidence (Acácio et al, 2005;Coppedè et al, 2006;Biselli et al, 2008b). We explored gene-gene interactions and found the first evidence of a positive interaction between the polymorphic variants of the MTHFR, MTHFD and TC genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Polymorphisms of genes that encode enzymes involved in folate metabolism have been associated with the etiology of DS. [9][10][11][12] A polymorphism of the reduced folate carrier 1 (RFC1) gene consisting of an adenine-to-guanine substitution at position 80 (A80G) has been associated with altered concentrations of products derived from the folate metabolic pathway. 13,14 This has been indicated as a maternal risk factor for DS, in combination with other polymorphisms involved in this metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 This has been indicated as a maternal risk factor for DS, in combination with other polymorphisms involved in this metabolism. 9,11 The RFC1 gene encodes the reduced folate carrier 1 protein, which plays a role in folic acid absorption, thereby transporting 5-methyltetrahydrofolate, the metabolically active form of folate, into a variety of cells. 15 Polymorphisms of genes encoding cobalamin-transporting proteins such as transcobalamin 2 (TC2) may interfere with the availability of this vitamin in the organism.…”
Section: Introductionmentioning
confidence: 99%